Management of bed availability in intensive care in the context of hospitalization by court order - Mara Ambrosina de Oliveira Vargas; Elizabeth Peter; Kely Regina da Luz; Edison Luiz Devos Barlem; Carla Aparecida Arena Ventura; Eliane Regina Pereira do Nascimento (Universidade de São Paulo, 2020)
Abstract Objective: to identify, from the nurse perspective, situations that interfere with the availability of beds in the intensive care unit in the context of hospitalization by court order. Method: qualitative exploratory, analytical research carried out with 42 nurses working in adult intensive care. The selection took place by non-probabilistic snowball sampling. Data collected by interview and analyzed using the Discursive Textual Analysis technique. Results: three categories were analyzed, entitled deficiency of physical structure and human resources; Lack of clear policies and criteria for patient admission and inadequate discharge from the intensive care unit. In situations of hospitalization by court order, there is a change in the criteria for the allocation of intensive care beds, due to the credibility of professionals, threats of medico-legal processes by family members and judicial imposition on institutions and health professionals. Conclusion: nurses defend the needs of the patients, too, with actions that can positively impact the availability of intensive care beds and adequate care infrastructure.